Effect of Indenter Displacement Onangle Plied Composite Plates Subjected to Quasi-Static Loading. (2015) - Kumar, M. Ashok; Prasad, A.M.K.; Ravishankar, D.V.; Sateesh, N.; Ravi, D.
Abstract: E-glass/Epoxy composite materialsare being orthotropic in nature, when subjected to quasi-static loading. These were considered to be poor in performance, when compared to isotropic materials. The damage caused by quasi-static indentation to the laminate is an important aspect to be studied. This mode of loading is very common pertaining to pressure vessels, oil and gas pipe line applications. In the present work, experimentation was carried out as per ASTM D 6264. In order to understand the failure behaviour of angle plied laminates, all the specimens were subjected to quasi-static loadingunder controlled ball indenter displacement.The damage patterns were analysed and compared withscanning electron micrographs. The experimentation was simulated and correlated with finite element method. Results reveal that fibre angle has a great influence on mechanical properties of composite materials.